An Examination of High-Achieving First-Generation College Students From Low-Income Backgrounds. (January 2018) - Hébert, Thomas P.
Experiences of 10 high-achieving first-generation college students from low-income backgrounds were the focus of this qualitative research study. Family adversity and difficult personal experiences during adolescence were major themes; however, students benefitted from emotionally supportive K-12 educators and academic rigor in high school. Sustained family pride helped to keep them focused on reaching their goals, as well as intellectual engagement at the university, and influential mentors. The 10 participants developed a strong sense of purpose at the university and graduated well prepared for careers and graduate school. Implications of the findings are presented along with suggestions for designing effective university experiences for talented first-generation students.